FAKTOR KOMPENSASI SUASANA ORGANISASI KEPEMIMPINAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. KASMIL KOSMOS BALI - Ni Ketut Narti; Ni Wayan Sukartini; Luh Made Wijayati; Anak Agung Raka Sitawati (Forum Manajemen STIMI Handayani Denpasar, 2013)
This research has three purposes. To know the availability orunavailability of the partial signiﬁ cant inﬂ uence of compensation, organizationalatmosphere, leadership and work characteristic factors toward work satisfactionof PT. Kasmil Kosmos employees. To know the availability or unavailability of asimultaneous signiﬁ cant inﬂ uence of the compensation, organizational atmosphere, leadership and work characteristic factors toward work satisfaction of PT. Kasmil Kosmos employees. To know the most dominant factors toward work satisfactionof PT. Kasmil Kosmos employees. The result of this research is anticipated to beused as a consideration in determining a policy in improving the employees’ worksatisfaction. The hypothesis are submitted in this research. Compensation, organizationalatmosphere, leadership and work characteristic factors that have a partial signiﬁ cantinﬂ uence toward work satisfaction of PT. Kasmil Kosmos employees. Compensation,organizational atmosphere, leadership and work characteristics factors that have asigniﬁ cant simultaneous inﬂ uence toward work satisfaction of PT. Kasmil Kosmosemployees. Respondents in this research are the entire 256 employees of PT.Kasmil Kosmos. The hypothestical examination is conducted by using the FactorRegression Model analysis technique, with its problem-solving technique whichis by an analysis factor and a multiple linier regression factor. By using SPSS forwindow 15 programme, the result shows that work satisfaction indicators of PT.Kasmil Kosmos employees have a high loading factor over 0.5806 so that all theseindicators can conﬁ rm and represent formation factors including: compensation,organizational atmosphere, leadership and work characteristics factors. Afterhaving been analyzed by applying the multiple linear regression technique, theresult shows that the compensation, organizational atmosphere, leadership andwork characteristic factors have a partial and simultaneous signiﬁ cance to worksatisfaction of PT. Kasmil Kosmos employees. This is shown by R 0.995 The mostdominant inﬂ uencing factor to work satisfaction of PT. Kasmil Kosmos employees isshown by the compensation factor at a value of beta coefﬁ cient of 0.273The implication of this research result may create a better work satisfaction ofemployees, so that the object of the organization seen from the manpower viewpointcould be realized. The company should remain to observe factors which may create work satisfaction, because by the existence of satisfaction in the work, employeeswill show good performance or quality of work so that employees will be moreproductive.